The Role of the Various Solvent Polarities on Piperine Reactivity and Stability - Ahmed, Lana; Omer, Rebaz (Niyazi BULUT, 2021)
Piperine is a natural cytotoxic agent aware of various therapeutic acts. The aim of this study is to look into the effects of solvent polarity on solvent-free energy, dipole moment, polarizability, and hyper-polarizability of the first order, as well as various molecular properties including chemical hardness and softness, chemical potential, electronegativity, and electrophilicity index, in order to gain a better understanding of its reactivity and stability. The Becke, 3-parameter, Lee-Yang-Parr (B3LYP) level of theory with the cc-pVDZ basis set was used to perform all forms of calculations in both the gas phase and in solution. The Solvation Model on Density (SMD) was used to measure the solvation-free energy, dipole moment, and molecular properties of five solvent systems: water, DMSO, ethanol, cyclohexane, and heptane. As the dielectric constant was reduced, the solving energies gradually decreased, i.e. free energy decreased with declining solvent polarity. Piperine's dipole moment has been found to increase when transitioning from non-polar to polar solvents. The dipole moment of piperine was greater than that of the gas phase in various solvents. PPN's dipole moment and first order hyper-polarizability gradually increased as the solvent polarity increased, while its polarizability decreased. In addition, the hardness, chemical potential and electrophilicity index were decreased from non-polar to polar solvent, but with the rise in solvent polarity for the PPN molecule, softness and electronegativity were increased. The determined free energy solvation, dipole moment, polarizability, hyper-polarizability of the first order, and molecular properties identified in this research may contribute to an understanding of the stability and reactivity of piperine in specific solvent systems.
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik